Integrasi Strategi Pedagogis dan Afektif dalam Pembelajaran Tahfidz untuk Meningkatkan Kualitas Hafalan Al-Qur’an Siswa - Ronika Witrianingsih (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the strategies of tahfidz teachers in improving students’ Qur’anic memorization quality through a literature review approach. Memorization quality is not merely measured by the quantity of verses memorized, but also includes accuracy of recitation, fluency, consistency in muroja’ah (revision), and long-term memory retention. This research employed a literature review method by examining national and international journal articles as well as relevant academic books published between 2020 and 2025. Data were analyzed using content analysis techniques to identify themes, patterns, and research gaps related to teachers’ strategies in tahfidz learning. The findings reveal that effective tahfidz teaching strategies can be classified into four main aspects: (1) structured and consistent implementation of repetition (tikrar), (2) reinforcement of muroja’ah and periodic evaluation, (3) motivational strategies and character development, and (4) innovative learning approaches integrating collaboration and educational technology. The tikrar method is proven effective in strengthening memorization retention when supported by systematic program planning. Furthermore, intrinsic motivation, a conducive learning environment, and varied instructional methods significantly contribute to maintaining students’ memorization stability. In conclusion, improving the quality of Qur’anic memorization depends not only on repetition frequency but also on the integration of pedagogical strategies, affective-spiritual approaches, and instructional innovation. This study provides a conceptual contribution to the development of more comprehensive and sustainable tahfidz learning strategies.